Similar Midterm Clinical Outcomes and Aortic Remodeling in Bifurcated and Straight Aortic Stent Grafts Used to Treat Isolated Abdominal Aortic Dissection. (August 2022) - Wang, Tun; Shu, Chang; Li, Quan-ming; Li, Ming; Li, Xin; He, Hao; Luo, Ming-yao; Fang, Kun; Dardik, Alan; Shi, Jing-cheng
Purpose: The optimal treatment for isolated abdominal aortic dissection (IAAD) is currently unknown. We compared the effects of straight and bifurcated aortic stent grafts on postoperative aortic remodeling in patients with IAAD. Materials and Methods: From February 2012 to December 2019, 57 patients with IAAD were treated using endovascular methods, including either a bifurcated or a straight aortic stent graft. The clinical features, risk factors, computed tomography angiograms, midterm follow-up results, and aortic remodeling of these patients were reviewed and analyzed. Results: In total, 44 (77%) patients were treated with a bifurcated graft and 13 (23%) patients were treated with a straight graft. Patients treated with straight grafts had fewer common iliac arteries involved (38% vs 73%, p=0.023), the dissection length was shorter (76.3 ± 40.0 vs 116.2 ± 56.7 mm, p=0.011), and the preoperative aortic diameter (26.0 ± 5.6 vs 35.2 ± 12.1 mm) and the false lumen diameter (13.1 ± 5.2 vs 21.2 ± 11.3 mm) were smaller. During the procedure, there were 3 (5.3%) type I endoleaks, 1 (1.8%) surgical conversion and 1 (1.8%) partial renal artery coverage without perioperative mortality. Patients with straight grafts had shorter operative time (96.5 ± 24.4 vs 144.2 ± 49.0 minutes, p<0.0001). The median follow-up duration was 37.6 ± 21.0 (range = 3–89) months with 1 (1.8%) aortic-related death. Type A aortic dissection occurred in 1 (1.8%) patient. New descending aortic dissection occurred in 3 (5.3%) patients, and 1 patient advanced to type A aortic dissection 3 months later. Two (3.5%) patients had limb occlusion. There was no significant difference in aortic remodeling, survival, and freedom from all adverse events between the 2 treatment strategies. Conclusions: Endovascular treatment provides a safe, minimally invasive treatment for IAAD in midterm follow-up. Compression of the true lumen at the aortic bifurcation is the main concern after treatment with a bifurcated graft. Straight grafts are an excellent alternative for some patients, with the benefit of reduced procedural time, effective aortic remodeling, and excellent clinical prognosis. More experience is needed to offer clear recommendations for making treatment decisions as well as determine long-term effectiveness and durability.